Pendekatan Diplomasi Energi Tiongkok Terhadap Venezuela - Yafie Shahna; Rika Isnarti (Papua Journal of Diplomacy and International Relations, 2022)
China remains the country with the most oil and gas consumption in the world. To meet its oil demand, China began exploring and diversifying imports. Venezuela is one of the countries that have close relations with China regarding trade and cooperation in the energy sector. In this regard, Venezuela requires China as an alternative source of oil trade export revenue after the sanctions imposed by the United States. This article analyzes China’s energy diplomacy in order to meet its demand for oil from Venezuela. By using the energy diplomacy concept, this study concludes that China’s energy diplomacy toward Venezuela is mostly carried out through a joint fund assistance system between China and Venezuela, known as the China-Venezuelan Joint Fund. The formation of the agreement is a form of guarantee for China in ensuring Venezuela would fulfill its obligations to export energy to China. Meanwhile, financial assistance from the cooperation agreement is also utilized to develop Venezuela’s energy infrastructure, thereby enhancing strategic relations between the two countries.KEYWORDSChina; China-Venezuelan Joint Fund; Energy Diplomacy; Venezuela